Analysis of Interest in Using Cryptocurrency as a Means of Payment in Indonesia - Rizky Hardian Adhinugraha; Johan Arifin (Publikasi Indonesia, 2024)
The purpose of this study is to find out whether cryptocurrencies can be used as a means of payment in Indonesia and also to find out how to grow interest in using cryptocurrencies in Indonesia. This is based on the convenience offered by cryptocurrencies. The research method used is a qualitative research method with a data collection method using semi-structured interview techniques. The data analysis method uses the analysis method according to Miles and Huberman. The results of the study reveal that Indonesia is currently still unable to use cryptocurrency as a means of payment. This is due to several key factors including regulatory unpreparedness and lack of cryptocurrency literacy for the public. The results of the study also revealed that an effective way to increase interest in using cryptocurrencies in Indonesia is to educate about cryptocurrencies and increase financial literacy to the public.